Behavioral response of spotted‐wing drosophila, Drosophila suzukii Matsumura, to aversive odors and a potential oviposition deterrent in the field. Issue 4 (12th June 2015) - Wallingford, Anna K; Hesler, Stephen P; Cha, Dong H; Loeb, Gregory M
Abstract: BACKGROUND: Drosophilia suzukii Matsumura is an invasive pest insect that lays its eggs in the fruit of several commercially grown crops. An effective oviposition deterrent could contribute to its management. Repellant odors were evaluated in the laboratory and in the field. RESULTS: Geosmin and 1‐octen‐3‐ol were found to be aversive to seven‐day‐old female D. suzukii at concentrations of 10 −1 and 10 −2 in laboratory choice tests. Field experiments found that fewer eggs were observed in fruit on the day of harvest and fewer adult D. suzukii were reared from fruit associated with 1‐octen‐3‐ol odors than control fruit in cultivated red raspberry. CONCLUSION: Geosmin and 1‐octen‐3‐ol induce aversive behaviors in Drosophila suzukii and are potential oviposition deterrents for its management in fruit crops. © 2015 Society of Chemical Industry